Adsorption kinetics of various gases in carbon molecular sieves (CMS) produced from palm shell - Ahmad, M.A.; Daud, W.M.A.W.; Aroua, M.K. (Elsevier, 2008)
Carbon molecular sieves (CMS) have been prepared from locally available palm shell of Tenera type by a thermal treatment technique involving carbonization followed by steam activation and benzene deposition technique. Carbonization of the dried palm shells was done at 900 °C for duration of 1 h followed by steam activation at 830 °C for 30-420 min to achieve activated carbons with different degree of burn-offs. The highest micropore volume of activated carbon obtained at 53.2 burn-off was found suitable to be used as a precursor for CMS production. Subsequent benzene deposition onto activated samples at temperature range from 600 to 900 °C for various benzene concentrations have resulted in a series of CMS with different kinetic selectivities. The molecular sieving behaviour of the CMS products was assessed by kinetic adsorption isotherms of O2, N2, CO2 and CH4 at room temperature.